The right tree for the job - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Nitrogen fixing trees for acid soils edited by Mark Powells 1996 110pp Nitrogen Fixing Tree Association, Winrock International 38 Winrock Drive, Morrilton, Arkansas 72110 9537, USA